Positive psychology and change : how leadership, collaboration and appreciative inquiry create transformational results - Lewis, Sarah, 1957- (Wiley, 2016)
Positive Psychology and Change explores how areas of positive psychology such as strengths, flow, and psychological capital can be applied to the everyday challenges of leading a dynamic and adaptive work community, and how collaborative group approaches to transformational change can be combined with a positive mindset to maintain optimism and motivation in an unpredictable working environment.